Computer science at secondary school: a systematic review on the teacher professional development in Argentina - Rodríguez, Jorge (2023)
The current study’s aim is to develop a systematic revision/ review on the Initial Teaching Formation in the Computing area for the Argentinian secondary education. a recopilation of the Superior Teacher Training Institutions, Non-University Institutions and Universities’ Study Plans and Curriculary Designs was made. as a result of it came a compilation of 17 curriculary proposals. In all cases, the training areas composition and the workload assigned to them was analised. The revision shows divergencies and continuities when comparing Non- University and University institutions as well as the fact that there were few available formation options for this disciplinar field.